2023
DOI: 10.1021/acs.jafc.2c07061
|View full text |Cite
|
Sign up to set email alerts
|

Structure and IgE Cross-Reactivity among Cashew, Pistachio, Walnut, and Peanut Vicilin-Buried Peptides

Abstract: Peanut and tree-nut allergies are frequently comorbid for reasons not completely understood. Vicilin-buried peptides (VBPs) are an emerging family of food allergens whose conserved structural fold could mediate peanut/tree-nut co-allergy. Peptide microarrays were used to identify immunoglobulin E (IgE) epitopes from the N-terminus of the vicilin allergens Ara h 1, Ana o 1, Jug r 2, and Pis v 3 using serum from three patient diagnosis groups: monoallergic to either peanuts or cashew/pistachio, or dual allergic.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Cashew nuts, pistachios, and peanuts have been studied more internationally, and allergenic protein fractions have been reported considerably. , Peanut and tree nut allergies are often comorbid and prone to cross-reactivity, possibly because of the structural features, the Vicilin-buried peptides (VBP) scaffolding in peanuts and tree nuts . Despite the considerable structural homology and amino acid sequence identity between nuts and peanuts, , and the potential cross-reactivity between nuts and Sichuan peppers, our study showed that serum IgE from Sichuan pepper-allergic patients binds to the 11S legume protein, as well as to the two nuts of cashews and pistachios apparently, but they did not bind to peanut extracts (Figure B,C).…”
Section: Discussionmentioning
confidence: 67%
“…Cashew nuts, pistachios, and peanuts have been studied more internationally, and allergenic protein fractions have been reported considerably. , Peanut and tree nut allergies are often comorbid and prone to cross-reactivity, possibly because of the structural features, the Vicilin-buried peptides (VBP) scaffolding in peanuts and tree nuts . Despite the considerable structural homology and amino acid sequence identity between nuts and peanuts, , and the potential cross-reactivity between nuts and Sichuan peppers, our study showed that serum IgE from Sichuan pepper-allergic patients binds to the 11S legume protein, as well as to the two nuts of cashews and pistachios apparently, but they did not bind to peanut extracts (Figure B,C).…”
Section: Discussionmentioning
confidence: 67%
“…38 The disulfide bond was a critical factor for maintaining conformational stability, and the preservation of disulfide bonds is crucial for the binding of IgE to allergens. 39 Zhou et al found that all disulfide bonds were destroyed and the allergenicity of the mutant was decreased when the C mutated into G. 40 In the previous study, the disulfide bond of Scy p 4 was destroyed by the DDT treatment, and the IgG-/IgE-binding activity of Scy p 4 was reduced, which indicated that the disulfide bond was important for IgE-binding to SCP. 15 In this study, C 97 A had the lowest immunoreactivity.…”
Section: Discussionmentioning
confidence: 94%
“…Site-directed mutation can be used to modify critical amino acids of disulfide bond sites, conformational epitopes, or calcium-binding sites into alanine, which is a good means of manipulating allergenic structure at the molecular level . The disulfide bond was a critical factor for maintaining conformational stability, and the preservation of disulfide bonds is crucial for the binding of IgE to allergens . Zhou et al found that all disulfide bonds were destroyed and the allergenicity of the mutant was decreased when the C mutated into G .…”
Section: Discussionmentioning
confidence: 99%
“…The structures of the cC3C of the VLP of Ara h 1, the two individual cC3C repeats of the VLP of Ana o 1 and Pis v 3, and three cC3C repeats of the VLP of Jug r 2 have been determined by NMR [104,105]. The structures of such cC3C are typical disulfide bond stabilized helix hairpins and the best model of the structure bundle of the second cC3C repeat of Jug r 2 is shown in Figure 1E.…”
Section: Food Allergensmentioning
confidence: 99%
“…The VLP was also referred to as vicilin buried peptide [104,105]. However, none of the known structures of vicilins included the VLP region of proteins.…”
Section: Food Allergensmentioning
confidence: 99%